PENGARUH STRUKTUR MODAL, LIKUIDITAS, DAN PERTUMBUHAN LABA TERHADAP KUALITAS LABA PADA PERUSAHAAN SEKTOR PERKEBUNAN - Ahmad Yuda (LPPM Universitas Bina Bangsa, 2023)
This study aims to examine how to improve capital structure, liquidity, and profit growth to the quality of profits. The population in this study is plantation sector companies listed on the Indonesia Stock Exchange. The sample used in this study was 16 companies with secondary data in the form of financial statements in 2019-2021. This research is a quantitative method research using multiple linear regression analysis. The results of this study concluded that the capital structure, liquidity and profit growth did not have a significant effect on the quality of profits